Masculine Mask of Female Poetry: Z.N. Gippius and her Successors - Veronika B. Zuseva-Özkan (Studia Litterarum)
The article deals with the masculine personas in the poetry of female authors Z.N. Gippius and M.Ye. Levberg. The article examines possible reasons for adopting a masculine mask, and the desire to acquire subjectivity appears to be the most likely among them. This subjectivity within the frame of the masculine gender order of Modernism could be attained only through the appropriation of the male voice. The article discusses critical reception of such appropriation. The article discusses critical reception of such appropriation and establishes the influence of Gippius on Levberg’s poetry. In view of exetremely low fame of this author, the article provides her biography and introduces previously unpublished texts. The article examines principles of constructing the masculine lyrical persona by Levberg; which turns out to be the mask of a warrior, or, more specifically, of a knight (which is not tipycal for Z. Gippius). The author draws parallels with Levberg’s theatre plays. She concludes that, as is in Gippius’ case, the artistic work of Levberg is based on the transgression of the gender order with the aim of constructing her authorship and the respectable position in the aesthetic discourse. The author of the article demonstrates that the masculine persona of both female writers is not so much a “mask,” a temporary role, but a reflection of their life position, their urge to destroy the dominating gender order and to acquire aesthetic subjectivity.